INHIBITORY EFFECT OF CHITOSAN OLIGOSACCHARIDE ON HUMAN HEPATOMA CELLS IN VITRO - Liu, Likun; Yi, Xin; Liu, Jia; Zhang, Ershao; Weiling, Li (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Chitosan oligosaccharide, the degradation products of chitin, was reported to have a wide range of physiological functions and biological activities. In this study, we explored the inhibitory effect of Chitosan oligosaccharide on human hepatoma cells Materials and Methods: MTT assay was applied to detect cell viability of the human hepatoma cells treated with Chitosan oligosaccharide. Flow cytometric analysis was used to investigate the apoptosis of the human hepatoma cells treated with Chitosan oligosaccharide. We employed western blot to investigate the underlying mechanisms involved in the apoptosis. Results: Our data indicated that chitosan oligosaccharide dose-dependently inhibited the growth of hepatoma cells and induced apoptosis. On the molecular level, chitosan oligosaccharide decreased Bcl-2 and increased Caspase-3 expression which may be related to the apoptosis of hepatoma cells. Conclusion: Our results provide an experimental basis for the clinical development of Chitosan oligosaccharide as a novel anti-hepatoma drug.